Annual maintenance budget estimation for a plant system: Digraph model and matrix approach. Issue 2 (6th May 2014) - Gupta, Piyush; Gupta, Shashank; Gandhi, O.P.
Abstract : Purpose: – The purpose of this paper is to propose a methodology to evaluate the annual maintenance budget (AMB) for a plant system as a percentage of its asset replacement value (ARV). Design/methodology/approach: – Variables influencing the budget for the plant system are identified and modeled in terms of a plant maintenance Budget digraph. The nodes in the digraph represent the function of budget influencing variables and edges represent the degree of influence among these. The plant maintenance budget function is derived from the equivalent matrix of the plant maintenance budget digraph and is used to evaluate the AMB for the plant system as a percentage of its ARV. The presented model is illustrated with an example. Findings: – The proposed methodology enables the maintenance managers and practicing engineers to evaluate the AMB for maintenance tasks based on plant specific variables that can vary from one plant to another, without resorting to general rules-of-thumb method of budgeting or to expert judgment. Research limitations/implications: – The methodology suggested does not claim to cover all aspects of budgeting and is confined to direct maintenance costs. Practical implications: – A fair estimation of AMB for a plant system gives an appropriate direction to maintenance actions and ensures that the assets will be kept in healthy and reliable state. This is desirable because it will ensure that maintenance resources are appropriately benchmarked and the resources are utilized judiciously. This ensures maintenance effectiveness. Originality/value: – The paper presents a structural approach to budgeting for maintenance tasks. This approach is valuable for plant managers, with ease in implementation.